Secure supply and demand relationship perception routing in intermittently connected wireless networks - Peng YANG; Yang TANG; Na SHU; Ru-yan WANG (Tongxin xuebao)
Because of low message delivery probability and nodes malicious attack behaviors in the quota-limit routing for intermittently connected wireless networks,a secure routing is proposed based on supply and demand relationship perception.According to activity degree,average residual buffer ratio of neighbors and encountered nodes reputation dynamically perceived by nodes,the encountered nodes in real time build the supply and demand model and determine the message quota allocation combined with the message survival ratio in common.When network status meets constraint situations,update message quota dynamically based on demand elasticity of message.Simulation results show that the proposed strategy effectively reduces influence of nodes malicious behaviors and improve network performance greatly.